THE RELATIONSHIP OF ANEMIA AND NUTRITIONAL STATUS WITH QUALITY OF LIFE AMONG ADOLESCENT GIRLS IN WEST JAKARTA - jihan astuti (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2025)
Adolescent girls are at increased risk of anemia due to rapid growth, hormonal changes, and regular menstrual blood loss. Anemia may result in fatigue, psychological disturbances, reduced self-esteem, and impaired social functioning, all of which can diminish quality of life. However, the extent to which anemia severity and nutritional status influence quality of life remains unclear. This cross-sectional study examined the relationship between anemia severity, nutritional status, and quality of life among adolescent girls. The sample comprised 111 girls diagnosed with anemia at a Primary Health Center, based on hemoglobin levels, selected through purposive sampling. Quality of life was assessed using the WHOQOL-BREF, which evaluates physical, psychological, social, and environmental domains. Data were analyzed using the Chi-square test. The findings indicated a significant association between anemia severity and overall quality of life (p = 0.048). In contrast, nutritional status, as measured by body mass index, was not significantly associated with either quality of life (p = 0.499) or anemia severity (p = 0.598). These results suggest that anemia severity is a key determinant of quality of life in adolescent girls, whereas nutritional status alone does not exert a substantial effect.